EKSISTENSI MURAL SEBAGAI AKTIVASI RUANG PUBLIK DI LINGKUNGAN KOTA PADANG - Muhammad Riski; Heldi Heldi (Universitas Negeri Padang, 2020)
The presence of murals can be found in several public spaces in Padang City. It's not something new, but the presence of mural still gets pros and cons. Murals in public spaces have different forms, techniques, functions and meanings because they affect the purpose and function of the place. The aim of the author is to examine the presence of murals in public spaces to describe the form (visual), techniques, function of murals, styles (patterns) and the meaning of murals in public spaces in Padang City, with the title